2018
DOI: 10.3390/su10061928
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Antecedents of Green Tourism Behaviors: A Case Study in Suburban Areas of Taipei, Taiwan

Abstract: Abstract:Understanding user behaviors is the foundation to support the design and development of a sustainably built environment. This exploratory study used a mixed method to explore people's perception, motivation, intention, and behaviors of green tourism in Taiwan. The qualitative approach explored intrinsic and extrinsic factors that could influence people's intention to participate in green tourism. The quantitative approach provided evidence of influencing factors of green tourism. The findings suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
1
13
0
1
Order By: Relevance
“…The items measured for our constructs were adapted from a previous study and modified to suit the objectives of this study. The green tourism construct was measured with six items, which were adapted from [115]; environmental concern was measured through four items, which were adapted from [116]; attitudes was measured with five items, and adapted from [115]; behavior was also measured with five items, which were adapted from [115]; intention to participate in sustainability of green tourism was measured with four items; one item adapted from [115] and three items adapted from [116]; subjective norms was measured with three items, and adapted from [116]; while perceived behavioral control was measured with three items, which were adapted from Chuang et al [86]. Subsequently, all the items were scaled with a five-point Likert scale, which ranged from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Instrument Developmentmentioning
confidence: 99%
“…The items measured for our constructs were adapted from a previous study and modified to suit the objectives of this study. The green tourism construct was measured with six items, which were adapted from [115]; environmental concern was measured through four items, which were adapted from [116]; attitudes was measured with five items, and adapted from [115]; behavior was also measured with five items, which were adapted from [115]; intention to participate in sustainability of green tourism was measured with four items; one item adapted from [115] and three items adapted from [116]; subjective norms was measured with three items, and adapted from [116]; while perceived behavioral control was measured with three items, which were adapted from Chuang et al [86]. Subsequently, all the items were scaled with a five-point Likert scale, which ranged from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Instrument Developmentmentioning
confidence: 99%
“…According to The Organisation for Economic Co-operation and Development (OECD) research [1], the skills and professions identified as particularly relevant for the green economy tend to be male dominated (p. 6). For the tourism sectors, it is critical to consider factors such as educational elements and attitudes of people toward green tourism [44].…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…To be successful in this marketing, detecting the customer behavioral intentions in purchasing green products is important as it can assist them in the decision-making process to receive high-quality services [6]. In addition, it is important to investigate the factors for tourists' intentions to participate in green tourism [7].…”
Section: Introductionmentioning
confidence: 99%